+0  
 
0
37
1
avatar+47 

Find $p+q$, given that $(q+4)(p+3)-(q+2)(p+1)=44$.

 Jun 23, 2021
 #1
avatar+148 
+1

i'm not CPhill, but here is my take on this problem:

 

first, let's expand and simplify the expression - 

 

pq + 3q + 4p + 12 - (pq + q + 2p + 2) = 44

pq + 3q + 4p + 12 - pq - q - 2p - 2 = 44

2q + 2p + 10 = 44

2q + 2p = 34

 

and when we divide both sides of the equation by 2, we get p + q = 17.

 

 

hope this helped! please let me know if you are confused about anything i did smiley

 Jun 23, 2021

2 Online Users